KARAKTERISTIK AWOT DALAM BERWIRAUSAHA MELON DI KELURAHAN KENTEN KECAMATAN TALANG KELAPA KABUPATEN BANYUASIN - Edisca, Vien; Sobri, Khaidir; Abubakar, Rafeah (Universitas Muhammadiyah Palembang, 2016)
Awot Characteristics in Entrepreneurship in Sub Kenten Melon District of Talang Kelapa Banyuasin. The purpose of this study was to determine the characteristics of operating Awot melon in Sub Kenten Subdistrict Talang Kelapa Banyuasin. This research was conducted in the Village District of Talang Kelapa Kenten Banyuasin. In March to May 2016. The method used was a case study, for example the withdrawal method is done deliberately (proposive). Data collection methods used in this study is the observation and direct interview to the respondents who have been determined by using tools such as questionnaires that had been prepared in advance. Processing data using qualitative descriptive analysis. The results showed that the characteristics of awot include confidence, perseverance, hard work, self-contained and terkatagori moderate level characteristics.